Perhitungan Premi Murni Kendaraan Bermotor Menggunakan Generalized Linear Models - Romantica, Krishna Prafidya; Paiz Jalaludin (Haka Vyza Media, 2023)
Insurance is a form of agreement between the insurer against the insured party (insurance company), where the insurer will pay a premium to the insured every month as a form of collateral for loss or damage that befalls him for certain events. Researchers took data by distributing questionnaires to respondents. Some covariate variables used in the study include: gender, vehicle age, vehicle insurance costs, vehicle use, vehicle mileage every year, and claims records in the last three years. Meanwhile, the dependent variable is frequency claim and claim severity. The researcher estimates the Generalized Linear Models (GLZ) parameters using the maximum likelihood estimation (MLE). The next step, researchers conducted a model compatibility test on the dependent variable using calculations on the Akaike Information Criteria (AIC), where the model chosen was the model with the lowest AIC value. Based on this, the researcher can determine covariate variables that affect the dependent variable and model it. The final step is the researcher calculates the probability of claim frequency, claim severity, and estimates the amount of pure premiums charged to respondents.